CHRONIC HEPATITIS C WITH SIGNIFICANT MORBIDITY AND END-ORGAN DAMAGE DEVELOPMENT DURING PEG-INTERFERON ALPHA-2A/RIBAVIRIN THERAPY - Likmeta, Mirlinda; Shkoza, Artan; Zguri, Liridon; Kraja, Bledar (European Scientific Journal, ESJ, 2015)
Objective: To report a case of significant morbidity and end-organ damage development during Peg-interferon Alpha-2a/Ribavirin therapy. Case report: A 27-year-old woman patient with chronic hepatitis C diagnosis, genotype1b, Anti HCV positive, and HCV-RNA 6. 05 x 105 IU/mL, presented to our clinic in order to initiate the approved treatment regimen with subcutaneous peginterferon alfa 2a (PEG-INF-a2a, s.c.) plus oral ribavirin. There were no evident abnormalities in the patient’s physical examination and laboratory data prior to the treatment, except for general asthenia and arthralgias and, above normal biliriubin levels plus positive smooth muscle antibodies (SMA). The patient was started on 180 mcg PEG interferon alpha-2a s. c. once a week with ribavirin 1000 mg/day. Four months later, despite undetectable HCV-RNA, she developed anemia, neutropenia, thrombocytopenia, and high transaminase levels, due to which the staff opted for a half-dose of Peg-interferon Alpha-2a/Ribavirin. After that, she suffered deterioration in liver function (Child class C, MELD score = 23.4) in association with non-invasive predictors of liver fibrosis, and with common radiologic changes of liver cirrhosis. Conclusion: Patients with preexisting auto antibodies and chronic hepatitis C, especially women, may be predisposed to autoimmune hepatitis during interferon and ribavirin therapy. These patients require careful monitoring if IFN is considered as first line treatment.